(untitled) (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2024)
The Herbal lipsticks are composed of natural colourants and compounds to protect the lips. The market place for organic products in various fields extends throughout the world on account of increased awareness among consumers of side effects related to protracted use of some synthetic colouring compounds, and therefore the current trend towards healthful biomaterials in products. This work aimed to formulate a natural lipstick from coloured pigments of Nyctanthes arbor-tristis (Night flowering jasmine) flowers. The use of natural colouring pigments in the product would minimize the side effects. This study focused on the extraction of colourant from N. arbor-tristis flowers and optimizing the formula for the preparation of lipstick and evaluating it. The results indicate that the prepared formulation was good and had minimal or no side effects on the lips.